2019
DOI: 10.1186/s42834-019-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing ecological-economic efficiency of intensive shrimp farm through in-out nutrient budget and feed conversion ratio

Abstract: In aquaculture systems, insufficient nutrients impede shrimp growth while excessive amounts of nutrient inputs lead to environmental degradation and unnecessary high investment. A study of in-out nutrient budgets in an intensive Litopenaeus vannamei farm was conducted in this work to measure the amount of nitrogen (N) and phosphorus (P) input and output from the system. The feed conversion ratio (FCR) was obtained to determine the level of nutrient input performance. Between September and December 2017, monthl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 18 publications
0
11
0
1
Order By: Relevance
“…Shrimp farmers impose feed onto their shrimp in a targeted response to shorter harvest periods. This can cause overfeeding and water pollution (Chaikaew et al 2019). Nutrient concentrations in this study ranged from 0.20 to 1.25 mg.L -1 for nitrate and 0.01 to 0.08 mg.L -1 for orthophosphate.…”
Section: Physicochemical Water Quality Parametersmentioning
confidence: 76%
“…Shrimp farmers impose feed onto their shrimp in a targeted response to shorter harvest periods. This can cause overfeeding and water pollution (Chaikaew et al 2019). Nutrient concentrations in this study ranged from 0.20 to 1.25 mg.L -1 for nitrate and 0.01 to 0.08 mg.L -1 for orthophosphate.…”
Section: Physicochemical Water Quality Parametersmentioning
confidence: 76%
“…Silva et al (2006) stated differences found in nutrients result from many food processing operations that can directly or indirectly alter the level or chemical form of nutrients or their association with other components of the food. Chaikaew et al (2019) found that differences in the concentration of nutrients result from the type of system used in production, such as intensive and semi-intensive, which discharge more nutrients than the extensive system.…”
Section: Resultsmentioning
confidence: 99%
“…Kualitas air yang buruk secara langsung memengaruhi nafsu makan udang windu, yang mengakibatkan berkurangnya fungsi pencernaan usus dan berkurangnya pencernaan nutrisi di usus sehingga meningkatkan RKP. Seperti dikatakan oleh Chaikaew et al (2019) bahwa RKP dipengaruhi oleh kualitas air dan pengelolaan pakan pada budidaya udang. Selanjutnya Huet & Timmermans (1994) menyatakan bahwa RKP juga dipengaruhi oleh sintasan, kepadatan, bobot individu, perbedaan persentase makanan harian, waktu, dan lokasi budidaya, serta pertumbuhan biomassa udang.…”
Section: Produksi Udang Winduunclassified